A kantian reading of aesthetic freedom and complete human nature nourished through art in a classical Chinese artistic context. Issue 2 (3rd April 2019) - Hu, Xiaoyan
ABSTRACT: In this paper, I will show that classical Chinese artists adopted either Daoist or Chan Buddhist meditation to cultivate their mind to be in accord with the Dao, and that their view of the detached mental state as an ideal mental state for art appears to fit in with Kant's notion of aesthetic freedom. Even though it might be claimed that sensibilities are stressed over rationality in the classical Chinese artistic tradition, I suggest that the detached mental state cultivated through Daoist or Chan Buddhist meditation and experienced in artistic practice helps artists restore a balanced human nature. By projecting Schiller's account of the play drive, and the account of aesthetic freedom he developed from Kant's ideas, into the classical Chinese artistic context, I attempt to explain the balanced nature realised through artistic play by classical Chinese artists and point out the differences behind the parallels between these two approaches.